Effects of the fertilizer and water management on amino acids and volatile components in Cabernet Sauvignon grapes and wines - Zhang, Kui; Kang, Wenhuai; Han, Weihua; Ma, Haijun; Gong, Daozhi; Qin, Ling (International Journal of Agricultural and Biological Engineering, 2024)
The amino acids and the volatile substances in grapes and wines play important roles in their quality, and the concentrations of these substances can be changed by how a vineyard is managed, e.g., irrigation and fertigation regimes. This study aimed to evaluate the effect of fertilizer and water management on the distribution of amino acids, the volatile component profiles, and the sensory characteristics of Cabernet Sauvignon grapes and wines. The results showed that the amino acid concentration in grape berries was the highest under the 100% local fertilizer rate (HF) and 100% water irrigation quota (HW) treatment, and the volatile component concentration in wine was the highest under HF and 80% water irrigation quota (MW) treatment. The effect of irrigation on the amino acid content in grapes was greater than that of fertigation. The synergistic effect of fertilizer and water on arginine, serine, and glutamine in grape berries was significant. The interactive effect of fertigation and irrigation on the volatile substance in grapes was greater than that of fertigation and irrigation alone. The influence of irrigation on volatile substances in wines was greater than that of fertigation. In addition, there was also a correlation between the concentrations of multiple amino acids in grapes and volatile components in wines. Principal component analysis showed that the wine from the HFMW treatment had the best quality among all treatments. Keywords: fertilizer and water management, grape, wine, amino acids, volatile components DOI: 10.25165/j.ijabe.20241701.8034 Citation: Zhang K, Kang W H, Han W H, Ma H J, Gong D Z, Qin L. Effects of the fertilizer and water management on amino acids and volatile components in Cabernet Sauvignon grapes and wines. Int J Agric & Biol Eng, 2024; 17(1): 69-79.